Developing the evidence base for applying pharmacogenomics: proceeds from DIA Workshop IV –– Breakout Session 1. (January 2009) - Armstrong, Martin; Bromley, Christina; Cohen, Nadine; Hunt, Christine M; O''Neill, Robert; Power, Aidan
The 4th Drug Information Association Workshop in a series of workshops on Pharmacogenomics: ''Biomarkers and Pharmacogenomics in Drug Development and Regulatory Decision Making'' took place on December 10––12, 2007 in Bethesda, MD, USA. A number of breakout sessions were conducted to focus on different aspects of the development of biomarkers. Breakout Session 1 considered the evidence base for the development of pharmacogenomic markers from both safety and efficacy perspectives, with a view to understanding the challenges in the design of appropriate clinical studies during drug development. Case studies based on data generated during all stages of drug development were used to stimulate discussion and refine considerations for what constitutes a sufficient evidence base to support the effective use of novel, pharmacogenomic biomarkers. The discussions were open and lively, and some broad principles were drawn from the discussion. In this article, we summarize the case studies presented and develop key discussion points that arose out of the meeting. These case studies help to illustrate the current state of the art in the application of pharmacogenomics in drug development and the challenges being faced in the development of pharmacogenomics from interesting, exploratory associations into predictive biomarkers with clinical utility. We hope that this will serve as a stimulus to consideration of the critical issues facing the implementation of pharmacogenomics into drug development.